Temporal Lobe Intraparenchymal Retained Foreign Body from Remote Orbital Trauma - Aulino, Joseph M.; Gyure, Kymberly A.; Morton, Andrew; Cole, John W. (American Journal of Neuroradiology, 2005)
Summary: We present the case of a 35-year-old man with a new onset of seizure disorder who was found to harbor an intraparenchymal retained foreign body related to remote orbital trauma. Imaging revealed a rim-enhancing anterior medial temporal lobe mass. Histologic evaluation of the resected mass showed evidence of acute and chronic inflammation with associated foreign material. The patient described a “bar fight” 16 years previously in which he received a blow to the orbit with a pool cue stick. The diagnosis of a foreign body reaction should be considered when an intraparenchymal mass is identified in this location.